ORIENTASI DAN EKSPEKTASI METODE PENELITIAN KOMUNIKASI - Romlah; Riniyati; Ruswanto; Sumardi, Edi; Wardati, Ummu; Sobirin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the orientation and expectations of communication research methods within the framework of social science. Communication is understood as a meaning-laden social process; therefore, the selection of research methods becomes a crucial factor in producing valid and relevant scientific findings. This study employs a qualitative approach using a library research design, with data sources consisting of books and scholarly journal articles that discuss communication research methodologies, both qualitative and quantitative. The data were analyzed using a descriptive-qualitative technique through systematic classification and interpretation of methodological concepts. The findings indicate that communication research methods have distinct epistemological orientations, in which qualitative approaches emphasize the understanding of meaning and social context, while quantitative approaches focus on measurement and generalization of communication phenomena. The expectations of communication research methods encompass not only technical accuracy but also analytical depth, social relevance, and the ethical responsibility of the researcher. Thus, a comprehensive understanding of the orientation and expectations of communication research methods serves as an essential foundation for producing high-quality research that contributes to the development of communication studies.